2022
DOI: 10.3390/agronomy12051127
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Stress-Mitigating Effects of a Protein-Hydrolysate-Based Biostimulant Are Linked to Changes in Protease, DHN, and HSP Gene Expression in Maize

Abstract: The growth-promoting and heat-mitigating effects of a commercially available protein-hydrolysate-based biostimulant, Kaishi, during the early vegetative stage was investigated by applying it as a foliar spray on soil-grown maize plants or in the nutrient solution of hydroponically grown plants. At 10−3 dilution, the biostimulant inhibited germination and delayed the growth progress, while at 10−6–10−12 dilutions, it promoted shoot and root growth. Heat stress caused biomass reduction, decreased leaf pigment co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Several studies demonstrated that plant priming with microbial and/or non-microbial biostimulants results in enhanced plant defense response to stresses such as increased antioxidant enzymes activities, accumulation of polyphenols and osmolytes ( Shukla et al., 2019 ; Vaseva et al., 2022 ). Table 1 represents an overview of the molecular, metabolic, and physiological mechanisms underlying biostimulants-induced abiotic stress alleviation.…”
Section: Mechanism Of Action Of Biostimulants For Mitigation Of Abiot...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies demonstrated that plant priming with microbial and/or non-microbial biostimulants results in enhanced plant defense response to stresses such as increased antioxidant enzymes activities, accumulation of polyphenols and osmolytes ( Shukla et al., 2019 ; Vaseva et al., 2022 ). Table 1 represents an overview of the molecular, metabolic, and physiological mechanisms underlying biostimulants-induced abiotic stress alleviation.…”
Section: Mechanism Of Action Of Biostimulants For Mitigation Of Abiot...mentioning
confidence: 99%
“…PH (LISIVEG ® and GHI_16_VHL) also promote osmoregulation to increase tolerance to drought and salinity in C. annuum and Lactuca satuca ( Lucini et al., 2015 ; Agliassa et al., 2021 ). Moreover, these plant-derived biostimulants (alfa-alfa derived protein hydrolysate and Kaishi ® ) act at the photosynthesis and growth level by increasing protein production, glutamine synthetase (GS) and glutamate synthase (GOGAT) activities to improve salinity tolerance ( Ertani et al., 2013 ), and protein degradation protection and starch maintenance for thermotolerance in Zea mays ( Vaseva et al., 2022 ). Under salinity stress, the animal-derived PH Stressal is reported to lower chloride uptake and translocation to aerial parts, therefore reducing leaf necrosis symptoms in Diospyros kaki ( Visconti et al., 2015 ).…”
Section: Mechanism Of Action Of Biostimulants For Mitigation Of Abiot...mentioning
confidence: 99%
See 1 more Smart Citation
“…The action mechanism of PH involves stimulation of the plant antioxidant defense system and the photosynthesis. Concerning the antioxidant protection, PH upregulate the expression of phenylalanine ammonia lyase (PAL), heat shock proteins (e.g., HSP16.9, HSP22 and HSP116.9) and dehydrins (e.g., DHN2, DHN2, DHN4, DHN13 and DHNCCor410) genes, increase the antioxidant enzyme activities (SOD and APX), and the production of stress defence metabolites like terpenes, carbohydrates, amino acids and flavonoids, that control ROS overaccumulation, protect proteins and increase membrane stabilization [68]. Moreover, PH promote the photosynthesis and growth by stimulating pigment synthesis and protein production [69].…”
Section: Protein Hydrolysatesmentioning
confidence: 99%
“…Vegetal-derived protein hydrolysates (PHs) are a particular category of PBs, formed by a mixture of soluble peptides and free amino acids with potential bioactive effects aimed at enhancing plant growth and nutrition as well as at improving tolerance to salt stress following leaves or roots application ( Colla et al., 2017 ). The mechanisms underlying the protective action of PHs in the salinity stress mitigation may include: i) regulation of key enzymes involved in the TCA-cycle and N-assimilation pathway ( Colla et al., 2017 ); ii) increased photosynthetic metabolism by the elicitation of hormone-like activities ( Di Mola et al., 2021 ); iii) modulation of the phenylpropanoids metabolism ( Bavaresco et al., 2020 ); iv) changes in the gene expression of certain stress-inducible proteins ( Vaseva et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%